Rip van winkle and the legend of sleepy hollow Level 1 - Irving, Washington; Murphy, Margaret; Hopkins, Andy; Potter. Jocelyn (England Pearson Education Limited, 2008)
This book presents the classic tale of a henpecked husband who escapes to the mountains and falls asleep for twenty years, along with the story of a superstitious schoolmaster who has a terrifying encounter with a headless horseman.
Keywords: Tham khảo